Transnational crossroads : remapping the Americas and the Pacific - Fojas, Camilla, 1971-; Guevarra, Rudy P., Jr (Borderlands and transcultural studies., 2012)
Through a comparative framework, this volume weaves together narratives of U.S. and Spanish empire, globalization, resistance, and identity, as well as social, labor, and political movements. Contributors examine multiethnic celebrities and key figures, migratory paths, cultural productions, and social and political formations among these three groups. Engaging multiple disciplines and methodologies, these studies of Asian American, Latin American, and Pacific Islander cultural interactions explode traditional notions of ethnic studies and introduce new approaches to transnational and comparative studies of the Americas and the American Pacific.